Autonomous Learning in EFL Classroom: Struggles and Initiatives of English Teachers in Public and Private Schools in Indonesia - Syifaya, Zulfa Aurellye Oldra; Suharyanto, S (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This study aims to find out how junior high school English teachers' strategies in implementing autonomous learning in both private and public schools. Autonomous learning means students' freedom to determine the learning they choose and can be responsible for the learning they choose. In this study, the focus is on the implementation of autonomous learning in private and public schools. Methodology: This study employs a comparative approach, utilizing qualitative analysis. The researcher conducted interviews with teachers from both private and public schools. Subsequently, the interviews were transcribed and evaluated using qualitative research methodologies. Subsequently, the investigation brought novel contributions to the field of autonomous learning research. Results: The study reveals that private schools have a distinct edge over public schools in terms of offering better facilities and closely monitoring students' learning progress to facilitate autonomous learning. Facilities and parental monitoring serve as incentives for students to engage in independent work. Public and private school teachers demonstrate their commitment to employing effective teaching methods to facilitate autonomous learning. Application/Originality/Value: The findings of this study aim to raise awareness among the government regarding the disparity between private and public schools. It is crucial to address this issue to ensure that there is no significant discrepancy in the implementation of autonomous learning in the future. Additionally, it is hoped that the government will provide assistance to public schools that lack adequate facilities for effective teaching and learning.